AESTHETIC EXPLORATION OF BAMBOO CRAFT DECORATIVE LIGHTS BASED ON THE CREATIVE INDUSTRY - Husni Mubarat (LPPMPP Institut Seni Indonesia Padangpanjang, 2022)
Crafts or crafts are one of the creative industry sectors. This sector has the opportunity to grow the community's economy, especially for artisans whose areas are available with bamboo plants. In general, the purpose of making decorative lighting products from bamboo, namely as an effort to provide creative ideas for creating decorative lights from bamboo to the community, so that it can stimulate people who have the potential of natural resources from bamboo to be creative, both aims to encourage industrial growth. Creative activities in rural areas, both through groups and individuals, with the hope of increasing economic welfare for rural communities, and thirdly supporting the tourism industry in rural areas. The methodology used is the first exploration, such as research on decorative lighting products from bamboo as a creative idea either directly or via the internet, secondly making several alternative sketches as a process to find the basic form of the work to be made, which is continued at the design stage, thirdly cultivating products with a chisel and joint techniques. The products produced consist of designs and several creations of decorative lights as a source of creative ideas for the creative industry community. Keywords: Exploration; Aesthetics; Creative; Industry; Bamboo.EKSPLORASI ESTETIK KERAJINAN BAMBU LAMPU HIAS BERBASIS INDUSTRI KREATIF AbstrakSeni kriya atau kerajinan merupakan salah satu sektor industri kreatif. Sektor ini memiliki peluang untuk menumbuhkan perekonomian masyarakat, khususnya bagi pengrajin yang daerahnya tersedia tumbuhan bambu. Secara umum, tujuan pembuatan produk lampu hias dari bahan bambu, yakni sebagai upaya untuk memberikan ide kreatif kreasi lampu hias dari bahan bambu terhadap masyarakat, sehingga dapat menstimulasi bagi masyarakat yang memiliki potensi Sumber Daya Alam dari bambu untuk berkreasi, kedua bertujuan untuk mendorong pertumbuhan industri kreatif di pedesaan, baik melaui kelompok maupun perorangan dengan harapan dapat meningkatkan kesejahteraan ekonomi bagi masyarakat desa, ketiga mendukung keberadaan bagi industri pariwisata di daerah pedesaan. Adapun metodologi yang digunakan adalah pertama eksplorasi, sperti riset terhadap produk lampu hias dari bambu sebagai ide penciptaan baik secara langsung maupun melalui internet, kedua membuat beberapa sketsa alternatif sebagai proses untuk menemukan bentuk dasar dari karya yang akan dibuat yang dilanjutkan pada tahapan desain, ketiga penggarapan produk dengan teknik pahat dan sambunga. Adapun produk yang dihasilkan terdiri dari desain dan beberapa kreasi lampu hias sebagai sumber ide kreatif bagi masyarakat pelaku industri kreatif.Kata kunci: Eksplorasi; Estetik; Kreatif; Industri; Bambu